(untitled) (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2014)
That study embodied an important aspect of the modern history of Hijaz during the duration extended from the late 19th century to the early of 20th century, giving a clear picture about the personality of Ali Haider Pasha, that personality inspired by the political enthusiasm in jumping to the principality and returning the glory of his ancestors Al Zaid in the internal affairs of Hijaz basing on his loyalty and sincerity to the unionists who found in him the best future alternative of Sherif Hussein bin Ali, yet many challenges confronted his desire, the most prominent of which were Al-Hussein power and the Arab loyalty for him as well as his relations with the British, which delayed the Ottoman project in change until the year 1916, when the latter announced the Great Arab Revolution on the Ottoman State, here the justifications became sufficient in the emirate of Sherif Ali Haider Pasha, and went to Hijaz so as to arrange his internal situations, but he failed in reaching Mecca due to the military operations occurring in the country during World War I, then he returned back from where he came. Thus, the role of that character ended and with it ended the principality forever.